Pembelajaran PAI bagi Anak Autis Berwawasan Teknologi Pendidikan - Guntur Cahyono (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This research aims to exhibit the learning process of students with autism on the subject of Islamic religious teaching (PAI). This subject is a main course in every level of education including special need education for students with autism. Autism itself is an inheritaged condition during infancy or early childhood that creates difficulty in normal communication and social relation. The result shows that to accommodate the learning process for students with autism, the visual based technology is required to drill and reinforce the materials. The tools can provide visuals and reality that function as demonstration.